Distribution profiles of per- and poly fluoroalkyl substances (PFASs) and their re-regulation by ocean currents in the East and South China Sea. Issue 1 (15th December 2017) - Zheng, Hongyuan; Wang, Feng; Zhao, Zhen; Ma, Yuxin; Yang, Haizhen; Lu, Zhibo; Cai, Minggang; Cai, Minghong
Abstract: We investigated the distribution of 17 individual per- and polyfluoroalkyl substances (PFASs) in 42 surface water samples collected from the East and South China Seas (7.0–36.0°N, 110.0°N–123.0°E). Concentrations of 7 individual PFASs, including perfluorobutane sulfonate (PFBS), perfluorohexane sulfonate (PFHxS), perfluoropentanoic acid (PFPA), perfluorohexanoate (PFHxA), perfluoroheptanoate (PFHpA), perfluorooctanoic acid (PFOA), and perfluorooctane sulfonamide (FOSA), were quantified in the East China Sea, but only concentrations of PFOA and FOSA were quantified in the South China Sea. The total concentrations of the 17 PFASs ranged from 181 to 2658 pg/L in the East China Sea and from 62 to 494 pg/L in the South China Sea. We also show that river fluxes and ocean currents had a strong influence on the distribution of PFASs in the East China Sea. Using ArcGIS 10.1, we show how ocean currents control the spatial distribution of PFOA in the central South China Sea. Graphical abstract: Distribution of the total PFASs and ocean currents in the East and South China Sea. Highlights: Providing evidence for the occurrence and fate of PFASs in surface water in the East- South China Sea PFOA was dominating in the East China Sea while FOSA was abundant in the South China Sea. Ocean currents showed strong re-regulation on the distribution of PFOA in the South China Sea. The East China Sea suffered a worse pollution of PFASs than the South China Sea.